Positivity groundbreaking research to release your inner optimist and thrive - Fredrickson, Barbara 1964- (Oneworld, 2011)
A psychologist explains how to create a richer, healthier, more fulfilling life through a process called the upward spiral that incorporates innovative techniques for using positivity to influence relationships, health, and work
Originally published: 2010
Hier auch später erschienene unveränderte Nachdrucke
Keywords: Lebensführung; Selbstverwirklichung; Positive Psychologie; Positive psychology; Self-actualization (Psychology); Optimism; Psychology